2013
DOI: 10.1063/1.4790276
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 10 zJ energy dissipation of adiabatic quantum-flux-parametron logic using a superconducting resonator

Abstract: Adiabatic quantum-flux-parametron (AQFP) logic has the potential to operate with an ultimately small bit energy of several zeptojoules; however, this is too small to measure by conventional techniques. We measure such a small energy dissipation by coupling a superconducting resonator with an AQFP gate, where the insertion loss is sensitively varied with the small dissipation due to the very high Q factor of the resonator. We designed and implemented a 5 GHz superconducting resonator coupled with an AQFP gate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 16 publications
1
42
0
1
Order By: Relevance
“…Among these devices, AQFP logic is very energyefficient and can achieve sub-I c Φ 0 bit-energy operation because of adiabatic switching. We measured the energy dissipation of an AQFP gate with critically-damped Josephson junctions and showed that its bit energy is ∼10 zJ at 5 GHz operation [6], which is only 170 k B T at 4.2 K where k B is the Boltzman constant and T is the temperature. Moreover, we simulated the energy dissipation of AQFP gates with underdamped junctions.…”
Section: Introductionmentioning
confidence: 99%
“…Among these devices, AQFP logic is very energyefficient and can achieve sub-I c Φ 0 bit-energy operation because of adiabatic switching. We measured the energy dissipation of an AQFP gate with critically-damped Josephson junctions and showed that its bit energy is ∼10 zJ at 5 GHz operation [6], which is only 170 k B T at 4.2 K where k B is the Boltzman constant and T is the temperature. Moreover, we simulated the energy dissipation of AQFP gates with underdamped junctions.…”
Section: Introductionmentioning
confidence: 99%
“…QFP circuits themselves are extremely energy-efficient superconducting circuits because they do not use any bias resistors wasting static power. In addition, adiabatic operation of QFP circuits were recently proposed, and ultralow energy consumption was demonstrated [6,7,8]. A possible application of the reconfigurable QFP circuits includes ultimately energy-efficient, real-time signal/information processing systems for scientific and technical computing and big data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Energy-efficient superconducting digital electronics, from the single flux quantum (SFQ) pulse logic families [2] with clock frequencies in the 100 GHz range, to the adiabatic logic families [3] with zeptojoule bit energy dissipation, function through the exploitation of magnetic phenomena such as single flux quanta and inductance. It is thus not surprising that such electronics are very sensitive to magnetic fields and currents induced by stray coupling.…”
Section: Introductionmentioning
confidence: 99%